PENDIDIKAN KESEHATAN CUCI TANGAN PAKAI SABUN (CTPS) PADA SISWA SD 100110 DI DESA SIUHOM - Arinil Hidayah (Universitas Aufa Royhan Di Kota Padangsidipuan, 2022)
One indicator of clean and healthy living behavior is handwashing with soap (CTPS), which is one of the sanitation measures by washing hands and fingers using running water and soap to prevent various diseases and break the chain of disease transmission. The aim of this research is to motivate children about the importance of washing their hands with soap and running water in order to increase their knowledge in the field of health, and to motivate them to apply it in their daily lives. The method used in this activity is the lecture method, socialization using posters and ending with conducting education on washing hands with soap. The research sample was 30 children of SD 100110 Siuhom. This CTPS counseling includes activities related to CTPS, the purposes and benefits of doing CTPS, when CTPS is carried out and the steps that are practiced in CTPS activities. The results of the counseling show that the children already understand the behavior of hand washing and are able to practice washing hands with soap properly and correctly. The children seemed enthusiastic in this activity. They follow every step of washing hands that we practice in front of the class and they are able to practice it. The conclusion of this activity is that it is hoped that children and teachers can realize the importance of cleanliness and are able to get used to clean and healthy living behavior from an early age, one of which is by getting used to washing hands with soap in a good and correct way.